Behavioral Measures to Assess Adolescent Sexual Communication with Partners: A Scoping Review and Call for Further Studies. Issue 1 (2nd January 2023) - Maheux, Anne J.; Widman, Laura; Hurst, Jeffrey L.; Craig, Elizabeth; Evans-Paulson, Reina; Choukas-Bradley, Sophia
ABSTRACT: Sexual communication with partners is important for adolescents' sexual and socioemotional well-being. Behavioral assessments of partner sexual communication capture the complex and nuanced process of communication and are commonly used with adults, yet the existing literature among adolescents overwhelmingly relies on self-report measures. In the current paper, we reviewed the literature on adolescent partner sexual communication, identifying 14 studies including 2, 043 participants ( M age = 16) that used behavioral assessments (i.e., dyadic observations, role-plays with confederates, role-plays with vignettes). We also identify key gaps in the current literature: First, only one study recruited couples; studies that assessed dyadic interactions largely relied on confederates. Second, assessments often assumed that participants engaged in heterosexual sex, and no studies specifically recruited LGBTQ+ adolescents. Third, behavioral tasks often involved assumptions of participants' sexual goals (e.g., desire to refuse sex) and focused almost exclusively on sexual refusal and condom negotiation. Additionally, coding schemes lacked standardization and micro-analytic strategies (e.g., coding change over time). Finally, observational methods have been almost exclusively used to assess intervention efficacy, rather than to understand associations between behaviorally-assessed communication skills and sexual outcomes or self-reported communication in basic research. We discuss recommendations for future research, including regular use of behavioral observation methods with diverse samples, to triangulate across multiple methodologies and identify correspondence between behavioral and self-report measures.